1986
DOI: 10.1107/s0108270186092466
|View full text |Cite
|
Sign up to set email alerts
|

The structure of ferrioxamine D1–ethanol–water (1/2/1)

Abstract: Abstract. C27H47FeN609, M r= 737.7, Pi, a = 15.035 (20), b= 16.240 (17), c= 7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…The aliphatic or aromatic amides of the primary amino group of the analogs are expected to exert a minimal effect upon hydroxamate deprotonation. X‐ray crystallography revealed that the amide hydrogen of acetamide DFO (COCH 3 ) hydrogen bonds with an amide carbonyl located in the ligand backbone 9 atoms away, and is removed from the vicinity of the hydroxamic acid groups 24…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The aliphatic or aromatic amides of the primary amino group of the analogs are expected to exert a minimal effect upon hydroxamate deprotonation. X‐ray crystallography revealed that the amide hydrogen of acetamide DFO (COCH 3 ) hydrogen bonds with an amide carbonyl located in the ligand backbone 9 atoms away, and is removed from the vicinity of the hydroxamic acid groups 24…”
Section: Resultssupporting
confidence: 86%
“…Moreover, additional energy is required for the hydrolyzed ferric ion to penetrate the shell of water molecules surrounding the more hydrophobic regions. Assuming that the three‐dimensional structure of acetamide DFO (COCH 3 ) is analogous to the butylamide derivative (COC 3 H 7 ), intramolecular hydrogen bonding of the amide hydrogen may position the additional hydrophobic acyl chain to sterically interfere with iron binding by the third hydroxamate group 24…”
Section: Resultsmentioning
confidence: 99%
“…The structures for DFOB and DFOD shown here are for their ferrioxamine complexes (Fe(III) complexed), with the Fe(III) center hidden for clarity. Crystallographic data for Fe-DFOB and Fe-DFOD are from Dhungana et al (2001) and Hossain et al (1986), respectively. DFOB and DFOD structures differ in their terminal groups.…”
Section: Methodsmentioning
confidence: 99%
“…These figures were drawn using Setor (37). (30). When bound to FhuD, ferrichrome, albomycin, and Desferal crystallize as the ⌳-cis complex and coprogen forms the ⌬-N-trans-cis conformation.…”
Section: Figmentioning
confidence: 99%